2013
DOI: 10.1007/s00406-013-0390-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain perfusion asymmetry in patients with oral somatic delusions

Abstract: Oral cenesthopathy is a somatic delusion or hallucination involving the oral area and is categorized as a delusional disorder, somatic type. The pathophysiology of this intractable condition remains obscure. In this study, we clarified the pathophysiology of oral cenesthopathy by evaluating regional brain perfusion. We performed single photon emission computed tomography (SPECT) using 99mTc-ethylcysteinate dimer in 16 subjects (cenesthopathy:control = 8:8). The SPECT images were visually assessed qualitatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 32 publications
0
24
2
Order By: Relevance
“…In particular, schizophrenia has been shown to be associated with lesser neurons in the left ventrolateral posterior nucleus, but not the right [38]. Furthermore, general leftward cerebral atrophy has also been associated with delusions [8], apathy, and agitation [9] in AD, as well as post-traumatic stress disorder [40] and hallucinations [41]. Importantly, Table 2 Associations between clinical scores and asymmetry of individual ventral thalamic subnuclei in patients with mild cognitive impairment or Alzheimer's disease Clinical measures the associations with leftward ventral thalamic atrophy observed in this present study remained even after controlling for global brain asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, schizophrenia has been shown to be associated with lesser neurons in the left ventrolateral posterior nucleus, but not the right [38]. Furthermore, general leftward cerebral atrophy has also been associated with delusions [8], apathy, and agitation [9] in AD, as well as post-traumatic stress disorder [40] and hallucinations [41]. Importantly, Table 2 Associations between clinical scores and asymmetry of individual ventral thalamic subnuclei in patients with mild cognitive impairment or Alzheimer's disease Clinical measures the associations with leftward ventral thalamic atrophy observed in this present study remained even after controlling for global brain asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 234/321 OC patients showed bilateral symptoms who were excluded from the present study, and left side unilateral symptoms were found in 69.2% patients with unilateral OC. Although no signi cant was found in this study due to the small sample size, the left dominant symptom laterality and the ipsilateral NVC would be key points for the next investigations considering right dominant asymmetric CBF in the patients with OC [6] [7]. Further studies combined with CNS and peripheral nervous system were required to investigate highly complexed pathophysiology of OC.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, the investigation by using SPECT also revealed that CNS might be involved. The right-dominant regional CBF (rCBF) asymmetry was observed in the callosomarginal, precentral, and temporal regions in the patients with OC [6]. Moreover, a signi cant right dominant asymmetry in the temporal and posterior cerebral regions was observed regardless of the presence of a history of depression, while the mean rCBF values of patients with depression were lower in several regions [7].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The concept of oral dysesthesia overlaps with that of medically unexplained oral symptoms/syndromes and complex oral sensitivity disorder , and includes so‐called oral cenesthopathy , burning mouth syndrome, atypical odontalgia, phantom bite syndrome, occlusal discomfort syndrome , formication, somatic symptom disorders, and somatic‐type delusional disorder affecting oral regions . Although several reports point to the etiology of oral dysesthesia and possible treatments , these are far from established. Therefore, oral dysesthesia often causes extreme frustration for both patients and health‐care providers, sometimes resulting in unfortunate struggles and discord between them .…”
mentioning
confidence: 99%